Atmospheric rivers: a mini-review - Gimeno, Luis; Nieto, Raquel; Vázquez, Marta; Lavers, David A. (Frontiers in Earth Science, 2014)
Atmospheric rivers (ARs) are narrow regions responsible for the majority of the poleward water vapour transport across the midlatitudes. They are characterized by high water vapour content and strong low level winds, and form a part of the broader warm conveyor belt of extratropical cyclones. Although the meridional water vapour transport within ARs is critical for water resources, ARs can also cause disastrous floods especially when encountering mountainous terrain. They were labelled as atmospheric rivers in the 1990s, and have since become a well-studied feature of the midlatitude climate. We briefly review the conceptual model, the methods used to identify them, their main climatological characteristics, their impacts, the predictive ability of numerical weather prediction models, their relationship with large-scale ocean-atmosphere dynamics, possible changes under future climates, and some future challenges.